Pictorial atlas of soil and seed fungi : morphologies of cultured fungi and key to species - Watanabe, Tsuneo , 1937- (CRC Press & Taylor Group, 2010)
""...Presents a large amount of work collected systematically over a long period of time.... Dr. Watanabe shares his experience acquired as a plant pathologist and mycologist specialized in soil and similar fungi over a long period of time....will soon become a standard reference in mycological libraries."--Liliane E. Petrini, Comano, Switzerland, in Sydowia" ""...a useful tool for all involved in mycological studies."--Journal of Plant Pathology" ""...some of the best methods, particularly for culture maintenance, that this reviewer has ever seen in print...Each specimen is very ably illustrated with one to six photographs of outstanding quality, which should allow easy identification...an outstanding book for individuals interested in soil and seed fungi or for plant pathologists."--J. Dawson, Pittsburg State University, in Choice"--BOOK JACKET